1993
DOI: 10.1111/j.1471-4159.1993.tb09805.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐Methyl‐d‐Aspartic Acid/Glycine Interactions on the Control of 5‐Hydroxytryptamine Release in Raphe Primary Cultures

Abstract: Glutamic acid and glycine were quantified in cells and medium of cultured rostral rhombencephalic neurons derived from fetal rats. In the presence of 1 mM Mg2+, NMDA (50 microM) significantly stimulated (by 69%) release of newly synthesized 5-[3H]hydroxytryptamine ([3H]5-HT). D-2-Amino-5-phosphonopentanoate (AP-5; 50 microM) blocked the stimulatory effect of NMDA. AP-5 by itself inhibited [3H]5-HT release (by 25%), suggesting a tonic control of 5-HT by glutamate. In the absence of Mg2+, basal [3H]5-HT release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
4
13
0
Order By: Relevance
“…First, the selective NMDA receptor antagonist CPP (Davies et al, 1986) at 20 µM had no effect on the electrically evoked 5-HT release and, second, NMDA, even at a concentration of up to 100 µM, did not inhibit the electrically evoked 5-HT release. When 10 mM NMDA was pressure-ejected into the nigral slices it released 5-HT (results not shown), which is in agreement with previously reported findings in the DRN (Becquet et al, 1993;Tao and Auerbach, 1996), but is in contrast to the early results in the SN (Reisine et al, 1982). Therefore, the MK-801-mediated potentiation of electrically stimulated 5-HT must involve other mechanism(s).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…First, the selective NMDA receptor antagonist CPP (Davies et al, 1986) at 20 µM had no effect on the electrically evoked 5-HT release and, second, NMDA, even at a concentration of up to 100 µM, did not inhibit the electrically evoked 5-HT release. When 10 mM NMDA was pressure-ejected into the nigral slices it released 5-HT (results not shown), which is in agreement with previously reported findings in the DRN (Becquet et al, 1993;Tao and Auerbach, 1996), but is in contrast to the early results in the SN (Reisine et al, 1982). Therefore, the MK-801-mediated potentiation of electrically stimulated 5-HT must involve other mechanism(s).…”
Section: Discussionsupporting
confidence: 92%
“…Where the role of NMDA on 5-HT transmission has been investigated (for example, in the DRN), application of glutamate resulted in the increase of neuronal discharge (Vandermaelan and Aghajanian, 1983;Vandermaelan et al, 1986;Levine and Jacobs, 1992) and an increase in 5-HT release in vitro (Becquet et al, 1993) or in vivo (Tao and Auerbach, 1996).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the cellular mechanisms underlying the neuroprotective effect of 5-HT 1A receptor activation remain unclear, a proposed mechanisms is the hyperpolarization of pyramidal neurons that inhibits the excitotoxicity by glutamate after cerebral ischemia (45). Previous studies have shown that 5-HT 1A receptor stimulation can modulate NMDA receptor-induced Ca 2+ influx (22,41), and other reports have provided evidence for functional interactions between NMDA channels and 5-HT 1A receptors (1,36), suggesting that 5-HT 1A receptors may serve as mediators of autoprotective mechanisms of the brain against the effects of excitatory amino acid overstimulation (28). Also it is known that one of the regulatory sites of NMDA receptor is the Ser897 of NR1 subunit and that PP1 is one of the enzymes that regulate the function of this receptor mediating its dephosphorylation (17,20,44,47).…”
Section: Discussionmentioning
confidence: 99%
“…Serotonergic 5-HT receptor activation may be responsible for the weakening of signal transduction dependent on NO and cGMP released by NMDA receptor activation as well as on arachidonic acid. Becquet et al observed that NMDA receptor activation stimulates the release of serotonin, and this effect is modulated by glycine (Becquet et al 1993 ). Serotonin via the 5-HT2 receptor reduces the cholinergic receptor-dependent increase in the release of IPs and the mobilization of intracellular calcium (Samochocki and Strosznajder 1995 ).…”
Section: The Ionotropic Glutamate Receptors Nitric Oxide and Schizomentioning
confidence: 97%